POWTOON APPLICATION: ITS EFFECT ON STUDENTS’ LISTENING COMPREHENSION - Zulfia Siskawati; Nenri Suci Rahmadani (Journal of English Education and Enterpreneurship (JEEP), 2022)
The purpose of this research was to investigate the effect of using Powtoon Application on Students’ Listening Comprehension. The research design was pre-experimental research. The population was the eleventh grade students at MA As-SyuhadaDuri XIII. In order to take the sample, total sampling was used. 19 students of the eleventh grade of MA As-SyuhadaDuri XIII were as samples. Listening test was administered for them to collect data of their Listening Comprehension. Then, the data were analyzed by using Paired Sample T-test. Based on the score gathered, it showed that tcount was lower than ttable. The finding of tcount was -5.718 while the level of significance of 5% : 2=2,5%=0,025 sig. (2 tailed ) was 2.060. It showed that -5.718 < 2.060 or tcount<ttable. It indicated Ha was accepted and Ho was rejected. Thus, it could be concluded that the use of Powtoon Application had a significant effect on students’ listening comprehension at the eleventh grade students of MA As-SyuhadaDuri XIII.